Heavy metals concentrations in stormwater and tilapia fish (Oreochromis niloticus) in Kuala Lumpur holding and storage SMART ponds - Alrabie, Nabeel Abdullah; Mohamat Yusuff, Ferdius @ Ferdaus; Hashim, Rohasliney; Zulkeflee, Zufarzaana; Arshad, Aziz; Azmai, Mohammad Noor Amal (Universiti Putra Malaysia Press, 2019)
The issue of heavy metal contamination in urban stormwater has become a major concern for environmental pollution control agencies worldwide due to toxic effects on aquatic organisms and human health. The aim of this study is to determine the levels of heavy metals (Pb, Cd, Cu, Cr and Zn) in surface stormwater and tilapia fish (Oreochromis niloticus) obtained from holding and storage ponds of the Stormwater Management and Road Tunnel (SMART) Project in Kuala Lumpur, Malaysia. Results have indicated that the concentrations of all heavy metals in stormwater were lower than the recommended water quality criteria established by the United States Environmental Protection Agency (US EPA). On the other hand, the concentrations of Cd, Cu, Pb and Zn detected in fish were below threshold values suggested by the Food and Agriculture Organization (FAO) and Malaysian Food Regulations (MFR) standards. Only Cr was much higher than FAO limits for fish consumption. Additionally, the content of Cr, Pb and Zn was higher in fish samples collected from holding pond compared to those in storage pond. As the study reflects that Cr in tilapia fish from SMART ponds is of a high concentration, certain harmful effects on human health may result. Accordingly, the research recommends avoiding fishing from ponds, as they accumulate a significant amount of waste consumed by the fish.